Patient with inguinal hernia containing the urinary bladder complicated by bladder stones. Issue 5 (30th June 2019) - Inage, Kota; Mizusawa, Hiroya; Mimura, Yuji; Shimizu, Fumiaki
Abstract : Introduction: We encountered a patient in whom bladder inguinal hernia complicated by bladder stones was incidentally diagnosed. Bladder inguinal hernia containing stones in the prolapsed bladder is rare and only two cases have been reported. Case presentation: The patient was an 82‐year‐old male in whom ascending colon cancer and inguinal hernia containing the urinary bladder were diagnosed based on abdominal computed tomography performed to examine anemia. The urinary bladder contained several small stones. Radical surgery for the hernia and lithotripsy of the urinary bladder were concomitantly performed with right colectomy. On stone analysis, the stones were found to be uric acid calculi. Conclusion: In the three patients with inguinal hernia containing the urinary bladder complicated by stones, including our patient, two‐stage urination, organic lower urinary tract obstruction, and prolapse of the urinary bladder reaching the scrotum were noted in all patients.